2019
DOI: 10.3390/jcm8111990
|View full text |Cite
|
Sign up to set email alerts
|

Rivaroxaban Effects Illustrate the Underestimated Importance of Activated Platelets in Thrombin Generation Assessed by Calibrated Automated Thrombography

Abstract: Background: The direct oral anticoagulant rivaroxaban inhibiting specifically activated factor X (FXa) causes delayed thrombin generation (TG) as measured by calibrated automated thrombography (CAT). The implications of these changes for assessing bleeding or residual prothrombotic risks of patients are unclear in the absence of a better understanding of the underlying mechanism. Methods: We compared platelet rich plasma (PRP) without or with prior collagen-induced platelet aggregation (agPRP) in the CAT assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 37 publications
3
10
0
Order By: Relevance
“…Factor Xa inhibitors were strongly related to the appearance of biphasic curves. It has been reported that FXa inhibitors show greater effect on the maximum concentration of thrombin formed (peak height) than on ETP [9]. Our study confirms that ETP was not different between the two groups of non-flat TG curve shapes [9,14].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Factor Xa inhibitors were strongly related to the appearance of biphasic curves. It has been reported that FXa inhibitors show greater effect on the maximum concentration of thrombin formed (peak height) than on ETP [9]. Our study confirms that ETP was not different between the two groups of non-flat TG curve shapes [9,14].…”
Section: Discussionsupporting
confidence: 85%
“…More recently, in an in vitro experimental setting, we explored the determinants of TG curve shapes in the presence of platelets and rivaroxaban. The study showed that TG in platelet rich plasma (PRP) from healthy donors spiked with rivaroxaban developed in biphasic TG curves as a result, from a dissociation between the amplification and thrombin-dependent propagation phase [9]. In the present study, we aimed to investigate the appearance of TG curves in PRP from acute VTE patients enrolled in the Genotyping and Molecular Phenotyping in Venous Thromboembolism project (GMP-VTE).…”
Section: Introductionmentioning
confidence: 99%
“…Thrombin is a powerful activator of PAR, and hence thrombin inhibition results in a decreased platelet reactivity. Studies using thrombin generation test (TGT) showed that in platelet-rich plasma with prior collagen-induced platelet aggregation TGT includes platelet ability to support thrombin generation in the presence of direct factor Xa inhibitors (rivaroxaban) [11]. Many studies addressed VET ability to detect the effects of DOAC, generally showing a prolongation of the clot formation time (R-time or CT) [12].…”
Section: Vet Platelet Function and Direct Oral Anticoagulants (Doac)mentioning
confidence: 99%
“…Recent work explored the use of collagen-induced platelet aggregation (agPRP) for TG measurements in the presence of FXa inhibitors. Compared to resting PRP, agPRP was shown to enable full platelet potential to support TG in an anticoagulated setting [37]. These findings highlight the distinction between platelet aggregation and procoagulant functions, and support the use of platelet-dependent TG as a tool to investigate drug effects on a cell (platelet)-based model of coagulation.…”
Section: Platelet-dependent Thrombin Generation In Prothrombotic Condmentioning
confidence: 68%